Elite skiers' experiences of heat- and moisture-exchanging devices and training and competition in the cold: A qualitative survey - Jong, M.; Hanstock, H. G.; Stenfors, N.; Ainegren, M. (Health Science Reports, 2023)
Background and Aims Winter endurance athletes have a high prevalence of exercise-induced bronchoconstriction (EIB) and asthma, probably due to repeated and prolonged inhalation of cold and dry air. Heat- and moisture-exchanging devices (HME) warm and humidify inhaled air and prevent EIB. The aim of this study was to share cross-country skiers and biathletes' experiences of training and competition in low temperatures, views on temperature limits, usage of HME, and consequences of cold exposure on their health.